Variation in the age and environ mental structure of illiteracy residents of Al-Qadisiyah Governorate (Journal of the College of Basic Education, 2023)
The research aims to identify illiteracy in Al-Qadisiyah governorate spatial variation, according to the environment and age structure, at the governorate administrative units level.To achieve this, use quantitative and descriptive method, tabulat data and convert it in tables and percentages maps, charts and graphs for easy spatial comparison.